Prevalence of Molar Incisor Hypomineralisation Among School Children in Kavre - Shrestha, R; Upadhaya, S; Bajracharya, M (Kathmandu University Medical Journal, 2015)
Background Molar incisor hypomineralisation is defined as the hypomineralisation of systemic origin of one to four permanent first molars, and frequently associated with affected incisors. Till date, there is no data available on molar incisor hypomineralisation in any parts of Nepal. Objective To determine the prevalence and characteristics of Molar incisor hypomineralisation in 7 to 12 years old school children of Kavre. Method A total of 749 school children of age 7 to 12 years from four different randomly selected schools with at least one of the first permanent molars fully or partially erupted were evaluated using European Academy of Paediatric Dentistry criteria for molar incisor hypomineralisation. The examinations were conducted at respective schools by a single calibrated examiner. Result Molar incisor hypomineralisation was present in 13.7% of children. No gender differences were found.The mild type of defect (without structural loss of tooth) was the most prevalent type of molar incisor hypomineralisation with white/creamy demarcated opacities more frequent than yellow/brown demarcated opacities. Post eruptive breakdown was more in boys than in girls and this difference was statistically significant (p<0.05). Also, maxillary molars were affected more than mandibular molars and this difference was also statistically significant (p<0.05). Conclusion The prevalence of molar incisor hypomineralisation in Kavre was 13.7%.Demarcated opacities were more prevalent than breakdown. The hypomineralised defect was more prevalent in maxillary teeth than in mandibular teeth. The severity of defect increased with age and there was no difference in prevalence between girls and boys. Kathmandu University Medical Journal Vol.12(1) 2014: 38-42